Pemanfaatan Media Sosial Instagram Sebagai Media Pemasaran KR Vape Karawang - Dinar Reira Pelangi; Sri Alifiya Nurlaela Dewi; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Yayasan Daarul Huda Kruengmane, 2023)
Our purpose is to conduct an industrial visit to KR Vape Karawang to find out about the use of social media by KR Vape Karawang to promote its business ventures. The method we use is descriptive and observative by collecting some of the data we got from KR Vape and interviewing several questions about social media conducted by KR Vape Karawang. The results of the visit that we know from KR Vape by using Instagram as a platform for utilization (social media) by sharing several product posters and video advertisements. In this way, KR Vape can promote its products more effectively and efficiently without having to waste time and spend excess funds on marketing their business (digital marketing). The discussion we are conducting is contextual which is more directed at how KR Vape markets most of its products on social media (Instagram).